PUBLIC SERVICE INNOVATION THROUGH LANCAR D'DUKCAPIL 7311 LAO KEDESA AT THE POPULATION AND CIVIL REGISTRATION OFFICE OF BARRU REGENCY - Febby Febrianthy Mansur; Muh Darwis; Herlina Sakawati (Jurnal Aktor, 2026)
This study aims to determine public service innovation through LaNCAR D'DUKCAPIL 7311 LaO KeDesa at the Population and Civil Registration Office of Barru Regency. This type of research is descriptive with a qualitative approach. The data collection techniques used were observation, interview and documentation. Data analysis techniques, using an interactive model, namely data condensation, data presentation and conclusion drawing. The results showed that public service innovation through LaNCAR D'DUKCAPIL 7311 LaO KeDesa at the Population and Civil Registration Office of Barru Regency has been implemented well and has succeeded in creating quality public services for the community. This refers to the fulfillment of 4 aspects of innovation attributes, namely relative advantages that are superior to the previous licensing system, compatibility with the previous service system, the possibility of being tried through socialization, technical guidance, and ease of observation through an increase in the number of comparisons of ownership of population documents, while the factors that hinder the application of LaNCAR D’DUKCAPIL 7311 LaO KeDesa innovation are explained in the aspect of complexity, namely internet network stability.